Isla del Coco, on Cocos Plate, converges with Isla de San Andrés, on the Caribbean Plate, at 78mm/yr - Protti, Mariano (2012)
Isla del Coco is the only land mass of the Cocos Plate that emerges above sea level. This makes it the only place where Cocos Plate motion can be measured using Global Navigation Satellite System (GNSS) monitoring. Global Positioning System (GPS) observations have been carried out sporadically over more than two decades on Isla del Coco, allowing precise measurement of the motion of the Cocos Plate. Recently, in May 2011, a continuous GPS station was built and instrumented at Isla del Coco, in Wafer Bay, by OVSICORI-UNA and UNAVCO, as part of the COCONet regional GNSS network. Position time series from this CGPS station (ISCO: Isla del Coco) show a steady motion of Isla del Coco at a speed of 90.9±1.5mm/yr in the N35oE direction in ITRF2008 and convergence with the Caribbean Plate at 78±1mm/yr. This result is consistent with the findings of the earliest GPS studies, and agrees within uncertainty with the estimated convergence rate of 76.4±x mm/ yr of the MORVEL plate motion model. MORVEL is based on an average over the last 780,000 years, and our result suggests that Cocos-Caribbean plate motions have been constant over that time interval. Citation: Protti, M., V. González, J. Freymueller & S. Doelger. 2012. Isla del Coco, on Cocos Plate, converges with San Andres Island, on the Caribbean Plate, at 78mm/yr. Rev. Biol. Trop. 60 (Suppl. 3): 33-41. Epub 2012 Dec 01.